Contractual Structure of Structured Notes and Legal Characterisation of Non-Discretionary Trust - CHEN, Christopher Chao-hung (Institutional Knowledge at Singapore Management University, 2009)
This article argues that if a structured product is documented as “notes”, it should be deemed as “securities” under the Securities Exchange Act in Taiwan. It should be regulated issuance, purchase or brokerage activities under securities regulations, if a structured note is issued directly in Taiwan or if a domestic investor authorized a securities broker to have it purchased in a foreign country on his behalf,. In addition, even if one invests in structured notes issued by a foreign company via a non-discretionary trust with a commercial bank, this activity should still constitute sales of foreign securities; and thus it should require registration and/or authorization from competent authorities before issuance and a prospectus must also be provided. On this basis, we may further examine the regulation and conduct of business rules of promoting investment products by way of a non-discretionary trust under the name of wealth management.